Plant Developmental Biology Methods and Protocols - Hennig, Lars.; Hennig, Lars.; Köhler, Claudia.; Köhler, Claudia. (Methods in Molecular Biology,, 2010)
The beauty and variety of plants has fascinated mankind for thousands of years, and this fascination continues today as plant developmental biologists discover mechanisms that control the establishment of specialized cell types, tissues, and organs from the fertilized egg during a plant’s life. In Plant Developmental Biology: Methods and Protocols, expert researchers provide a collection of protocols for many of the common experimental approaches in plant developmental biology, including diverse methods that range from grafting over bimolecular fluorescence complementation to chromatin immunoprecipitation. Chapters are divided into six major parts: growth protocols, manipulation of gene activity, assaying developmental phenotypes, assaying gene activity, testing protein-protein interactions, and probing chromatin. Composed in the highly successful Methods in Molecular Biology™ series format, each chapter contains a brief introduction, step-by-step methods, a list of necessary materials, and a Notes section which shares tips on troubleshooting and avoiding known pitfalls. Comprehensive and revolutionary, Plant Developmental Biology: Methods and Protocols is an essential guide for all plant developmental geneticists, biochemists, and researchers in stress physiology and plant nutrition.